"Charles Taylor Responds". Issue 5 (20th October 2021) - Taylor, Charles
ABSTRACT: This article responds to the contributors to this special issue. I clarify my views on critical theory, capitalism, morality, sociality, secularity, subjectivity, and childhood. I close with some general remarks about the necessity for a hermeneutical approach to social, ethical, and political questions.